Application of Electronic Health Record (EHR) In Nursing Documentation: Literature Review - Ana Zakiyah; Iswati Iswati; Duwi Basuki (Adi Husada Nursing Journal, 2026)
Nursing documentation in Indonesia generally uses paper and has several limitations to completeness, efficiency, and accessibility of patient information. Electronic Health Record (EHRs)-based nursing documentation is an alternative to solving nursing documentation problems. This study aimed to analyze factors influencing the implementation of EHRs in nursing documentation and their impact on nursing services. This study used a literature review with the PICOS framework. Article search using electronic databases: Google Scholar, Research Gate, PubMed, and Science Direct with the keywords related to nursing documentation and EHRs. Articles published between 2019 and 2022 were screened based on inclusion and exclusion criteria, resulting in 10 eligible articles for review. The findings showed that the successful use of EHR-based documentation is determined by nurse perception factors, leadership and organizational support, availability of infrastructure, system usability and training to improve nurses' competence. EHR improves the quality of nursing care because it is more integrated, nurses feel satisfied because it is helped, and there is time efficiency in documenting nursing care.